Population-based study of event-rate, incidence, case fatality, and mortality for all acute vascular events in all arterial territories (Oxford Vascular Study). - Rothwell, P; Coull, A; Silver, L; Fairhead, J; Giles, M; Lovelock, C; Redgrave, J; Bull, L; Welch, S; Cuthbertson, F; Binney, L; Gutnikov, SA; et al. (2005)
BACKGROUND: Acute coronary, cerebrovascular, and peripheral vascular events have common underlying arterial pathology, risk factors, and preventive treatments, but they are rarely studied concurrently. In the Oxford Vascular Study, we determined the comparative epidemiology of different acute vascular syndromes, their current burdens, and the potential effect of the ageing population on future rates. METHODS: We prospectively assessed all individuals presenting with an acute vascular event of any type in any arterial territory irrespective of age in a population of 91 106 in Oxfordshire, UK, in 2002-05. FINDINGS: 2024 acute vascular events occurred in 1657 individuals: 918 (45%) cerebrovascular (618 stroke, 300 transient ischaemic attacks [TIA]); 856 (42%) coronary vascular (159 ST-elevation myocardial infarction, 316 non-ST-elevation myocardial infarction, 218 unstable angina, 163 sudden cardiac death); 188 (9%) peripheral vascular (43 aortic, 53 embolic visceral or limb ischaemia, 92 critical limb ischaemia); and 62 unclassifiable deaths. Relative incidence of cerebrovascular events compared with coronary events was 1.19 (95% CI 1.06-1.33) overall; 1.40 (1.23-1.59) for non-fatal events; and 1.21 (1.04-1.41) if TIA and unstable angina were further excluded. Event and incidence rates rose steeply with age in all arterial territories, with 735 (80%) cerebrovascular, 623 (73%) coronary, and 147 (78%) peripheral vascular events in 12 886 (14%) individuals aged 65 years or older; and 503 (54%), 402 (47%), and 105 (56%), respectively, in the 5919 (6%) aged 75 years or older. Although case-fatality rates increased with age, 736 (47%) of 1561 non-fatal events occurred at age 75 years or older. INTERPRETATION: The high rates of acute vascular events outside the coronary arterial territory and the steep rise in event rates with age in all territories have implications for prevention strategies, clinical trial design, and the targeting of funds for service provision and research.